2014
DOI: 10.1071/sr13334
|View full text |Cite
|
Sign up to set email alerts
|

Amending soil with sludge, manure, humic acid, orthophosphate and phytic acid: effects on aggregate stability

Abstract: Recycling of organic wastes via their incorporation in cultivated lands is known to alter soil structural stability. Aggregate stability tests are commonly used to express quantitatively the susceptibility of soil structural stability to deformation. The objective of this study was to investigate the effects of biosolids addition, namely composted manure (MC) and activated sludge (AS), and spiking of the soils with orthophosphate (OP), phytic acid (PA) or humic acid (HA), on soil aggregate stability of semi-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 41 publications
4
54
1
Order By: Relevance
“…Long-term fertiliser applications influence soil hydraulic properties by altering soil aggregates and structure (Zhang et al, 2006;Mamedov et al, 2014). Previous studies consistently showed that organic manuring increased soil aggregation and total porosity and reduced bulk density (Sommerfeldt and Chang, 1987;Schjonning et al, 2002;Arriaga & Lowery, 2003;Pagliai et al, 2004;Zhang et al, 2006;Saha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term fertiliser applications influence soil hydraulic properties by altering soil aggregates and structure (Zhang et al, 2006;Mamedov et al, 2014). Previous studies consistently showed that organic manuring increased soil aggregation and total porosity and reduced bulk density (Sommerfeldt and Chang, 1987;Schjonning et al, 2002;Arriaga & Lowery, 2003;Pagliai et al, 2004;Zhang et al, 2006;Saha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have reported decreases in aggregate stability following additions of biosolids, animal manure, or other organic amendments [44][45][46]. Degradation of aggregates and decreased stability may be due to biosolids composition, specifically the increase in compounds directly or indirectly involved in the dispersion of fine soil particles.…”
Section: Soil Water-stablementioning
confidence: 99%
“…Measurement of water-stable aggregates specifically addresses the potential for soil loss by water erosion and the potential to maintain soil structure which affects the transmission and retention of water. While organic amendments can increase soil aggregate stability by 1-to 10-fold, stability responses vary both spatially and temporally [4,9,11,13,15,44]. Stability will also be affected by application rate and frequency, though aggregate stability is not always positively correlated with application rate [11].…”
Section: Soil Water-stablementioning
confidence: 99%
See 2 more Smart Citations